Biotecnologia moderna e desenvolvimento humano sustentável: uma composição possível - Márcia Rodrigues Bertoldi (Araucaria)
This paper aims to analyze the modern biotechnology as a tool to sustainable human development. First, it examines the objects related to the theme of this study: the different conceptions of traditional and modern biotechnology - Biology changing - and the new environmental and economic: the right to sustainable human development. Then, the text analizes the interpretation of society, regarding the benefits and risks arising from the use of modern biotechnology to in the end, it discusses the possibilities defined in promoting the right to sustainable development through the use of this technique. The conclusion is that modern biotechnology is a tool designed to promote sustainable human development.